Politics in the New Hard Times : The Great Recession in Comparative Perspective - Lake, David A., 1956-; Kahler, Miles, 1949- (Book collections on Project MUSE., 2013)
"The Great Recession and its aftershocks, including the Eurozone banking and debt crisis, add up to the worst global economic crisis since the Great Depression of the 1930s. Although economic explanations for the Great Recession have proliferated, the political causes and consequences of the crisis have received less systematic attention. Politics in the New Hard Times is the first book to focus on the Great Recession as a political crisis, one with both political sources and political consequences. The authors examine variation in crises over time and across countries, rather than treating these events as undifferentiated shocks. Chapters also explore how crisis has forced the redefinition and reinforcement of interests at the level of individual attitudes and in national political coalitions. Throughout, the authors stress that the Great Recession is only the latest in a long history of international economic crises with significant political effects--and that it is unlikely to be the last."--Publisher's website.